Preferred Vocabulary Learning Strategies among Malaysian Students - Husin, Mohd Zulfadli Mat; Rahim, Nur Farah Asmaq Abdul; Ali, Zuraina; Alzeebaree, Yaseen; Bakar, Norsuhaily Abu (Research Journal in Advanced Humanities, 2022)
Vocabulary learning strategies (VLS) are essential to acquire and master English language skills. Previous research in the Malaysian context mainly focuses on students at the tertiary level, and a few on secondary school students. Thus, these studies have not thoroughly investigated the preferred VLS of secondary and tertiary ESL students. Examining the vocabulary-learning strategies preferred by ESL secondary and tertiary students in Malaysia is significant. VLS is important in determining Malaysian ESL students' English language communication performance. Quantitative convenience sampling methods were employed to determine the preferred VLS among Malaysian students. Data was gathered from 320 secondary school and tertiary colleges Malaysian ESL students using a revised Vocabulary Learning Strategies Questionnaires (VLSQ) version 6.4. Findings indicated that secondary and tertiary Malaysian students preferred metacognitive compared to other dimensions. Regarding gender, results showed significant differences between male and female students in meta-cognitive and cognitive VLS dimensions. In addition, secondary students preferred to use dictionaries, whilst tertiary students preferred using meta-cognitive regulation to learn new English vocabulary. These results show that students employed different VLSs in learning new vocabulary. Also, there is a significant difference between male and female students in VLS dimension preferences.